A Service Computing Manifesto: The Next 10 Years. - BOUGUETTAYA, ATHMAN; SINGH, MUNINDAR; HUHNS, MICHAEL; QUAN Z. SHENG; HAI DONG; QI YU; NEIAT, AZADEH GHARI; MISTRY, SAJIB; BENATALLAH, BOUALEM; MEDJAHED, BRAHIM; OUZZANI, MOURAD; CASATI, FABIO; et al. (Communications of the ACM, 2017)
The article discusses the challenges and strategies for the widespread adoption of service computing. Topics include the role of service computing in cloud computing, big data, the Internet of Things (IoT), and social and mobile computing, organizations' addition of service interfaces to their online services to improve accessibility and agility, and the emergence of web service technologies as a cross-disciplinary research field studying the science and technology underlying the IT service industry.